The healthy organization a revolutionary approach to people and management - Dive, Brian (Gale virtual reference library, 2004)
Reveals that the unhealthy features of both large and small organizations all stem from the same source, namely the lack of true decision-making accountability (DMA), and introduces a new approach to leadership development.